PENGARUH GAYA HIDUP DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK PONDâS PADA MAHASISWA PRODI PENDIDIKAN EKONOMI STKIP PGRI SUMATERA BARAT - Fitriani, Desi; Ramayani, Citra; Areva, Desi (Pendidikan Ekonomi, 2014)
ABSTRACTThis study aims to determine: (1) Lifestyles influence on purchasing decision pondâs cosmetics product, (2) Consumer attitudes influence on purchasing decision pondâs cosmetics product, (3) The inflence of lifestyle and consumer attitudes together on purchasing decision pondâs cosmetics product.Types of research used in this study is descriptive assosiative. When the study was conducted in November 2013. The populatio of this study is student education departement of economics STKIP PGRI western sumatera. The sample amounted to 92 people with a purposive sampling technique sampling. The data analysis technique used is multiple linear regresion.The results of this study indicate that, (1) Lifestyle significantly influence purchasing decision cosmetic product pondâs on student education departement of economic STKIP PGRI western sumatera. (2) Consumer attitude significantly influence purchasing decision cosmetic product pondâs on student education departement of economic STKIP PGRI western sumatera. (3) Lifestyle and Consumer attitude together significantly influence purchasing decision cosmetic product pondâs on student education departement of economic STKIP PGRI western sumatera.Â